Lateral release in hallux valgus deformity: from anatomic study to surgical tip - Hromádka, Rastislav; Barták, Vladislav; Bek, Jiří; Popelka, Stanislav; Bednářová, Jana; Popelka, Stanislav (The Journal of foot and ankle surgery, 2013)
The important part of hallux valgus deformity operations, especially in the case of an incongruent joint, is the release of the soft tissue on the lateral side of the first metatarsophalangeal joint. The purpose of the present anatomic study was, with preparation of the lateral structures of the joint and lateral conjoined tendon, to provide a background for a surgical tip of the release of the joint for an additional metatarsal osteotomy. For the present study, we used 30 specimens (15 left and 15 right) from 19 cadavers at the Institute of Anatomy, First Faculty of Medicine, Charles Faculty (Prague, Czech Republic). Only specimens that met the criteria of hallux valgus were included in the present study. The technique was based on the incision of the lateral sesamoid ligament and partial tenotomy of the lateral conjoined tendon from the first interdigital web space. The release was done gradually with supination and abduction of the big toe to achieve the smallest size of the tenotomy. The median of the tenotomy size of the conjoined tendon was 6.5 (range 5 to 14) mm. The median size of the conjoined tendon in the frontal plane just ventral to the sesamoid bone was 10.6 (range 8 to 14) mm. The technique of the release, in which the big toe was abducted and supinated, can minimize the size of the lateral conjoined tendon release and can minimize the possibility of a postoperative deformity.
Keywords: šlachy; Hallux; mrtvola; hallux valgus; Cadaver; Hallux Valgus; palec nohy; Humans; lidé; Osteotomy; Tendons; metatarzofalangeální kloub; osteotomie; Metatarsophalangeal Joint